HE EFFECT OF WATTPAD SOCIAL MEDIA AS ONLINE READING MEDIA ON INCREASING INTEREST IN READING FICTION IN ADOLESCENTS IN INDONESIA - Lubis, Isabela Estina Waty; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Through data released by BPS and UNESCO, the index of reading interest in Indonesian society is still categorized as low. Yet through the development of technology, reading activities can be done more easily. And one of the platforms that facilitate this reading activity is Wattpad. Wattpad is a website service and smart phone application, which allows users to read or submit work in the form of articles, short stories, novels, or the like.            This study aims to determine the effect of Wattpad social media on the interest in reading fiction in adolescents in Indonesia, using S-O-R theory. This research uses quantitative methods, with data collection techniques namely through questionnaires using Google Docs that are distributed online to Wattpad account users. The number of samples is as many as 135 respondents, with sampling using purposive sampling. To find out how much influence these two variables have, the researcher uses simple linear analysis. And for the processing of questionnaire data, the researchers used the Windows 23 Product And Service Solution (SPSS) Statistics program.            The results obtained in this study indicate that Wattpad social media on reading interest in adolescents in Indonesia obtained a regression coefficient of Y = 24,241 + 0.407X. The constant number (a) is 24,241 and the coefficient of the decision variable is 0.407. Meanwhile, t count 6.797 is greater when compared with t table 1.977, with a significance level of 0.000 smaller than α = 0.05. That is, there is the influence of Wattpad social media on the interest in reading fiction in adolescents in Indonesia. From the calculation results obtained a coefficient of determination (R2) of 0.258, which implies that the influence of the independent variable (Wattpad social media) on the dependent variable (reading interest) is 25.8% with a low category, while the remaining 74.2% is influenced by Other variables not included in this study. Thus Ha was accepted and Ho was rejected.